PENERAPAN MODEL KONSTRUKTIVISME UNTUKMENINGKATKAN BERPIKIR KRITIS SISWA PADA MATAPELAJARAN IPS DI KELAS V SDN 18 TUBUNG - Sepiana Rosita; Asep Eka Nugraha; Ahmad Khoiri (JURNAL PENDIDIKAN DASAR, 2020)
ABSTRACT(Bahasa Inggris) The general purpose of the research is to improve students' critical thinking by applying constructivism models in social studies learning on the material events of the arrival of westerners in class V of Elementary School Public 18 Tubung. The purpose of the research is specifically to improve (1) Planning learning by using constructivism models on social studies subjects to improve students' critical thinking (2) Implementation of learning by using constructivism models on social studies subjects to improve students' critical thinking (3) Students' critical thinking results by using the constructivism model on social studies subjects.This study used the classroom action research method, with the type of participant research. The research design uses the Kemmis and Mc Taggart models, namely planning, implementation, observation, reflection. The research instruments used were observation sheets for learning planning and implementation of learning, student observation sheets and student worksheets. The number of subjects in this study were 14 students consisting of 7 male students and 7 female students.The results showed: (1) The ability of teachers to plan learning increased to 0,19 from the average value of the first cycle of 3.38 while the second cycle of 3,57. (2) The ability of teachers in implementing learning shows an increase of 0,29 from the average value of the first cycle of 3,28 while the second cycle of 3,57. (3) The results of students' critical thinking also increased by 18,30, from the average value of the first cycle which is 62,50 while the second cycle of 80,80. Judging from the completeness value of student learning outcomes with Minimum Mastery Criteria (KKM) which is 60, in the first cycle the average value of 67,57 and the second cycle of 77,85 means that social studies learning material on the event of the arrival of the western nation has been declared complete has reached minimum completeness criteria, by applying constructivism learning models to social studies subjects about western events, students' critical thinking increases. Keywords: Application, Constructivism Model, Critical Thinking of Students, Social Sciences SubjectsABSTRAK Tujuan penelitian secara umum yaitu meningkatkan berpikir kritis siswa dengan menerapkan model konstruktivisme dalam pembelajaran IPS pada materi peristiwa kedatangan bangsa barat di kelas V SD Negeri 18 Tubung. Adapun tujuan penelitian secara khusus yaitu meningkatkan(1) Perencanaan pembelajaran dengan menggunakan model konstruktivisme pada mata pelajaran IPS untuk meningkatkan berpikir kritis siswa (2) Pelaksanaan pembelajaran dengan menggunakan model konstruktivisme pada mata pelajaran IPS untuk meningkatkan berpikir kritis siswa (3) Hasil berpikir kritis siswa dengan menggunakan model konstruktivisme pada mata pelajaran IPS.Penelitian ini menggunakan metode Penelitian Tindakan Kelas, dengan jenis penelitian partisipan. Desain penelitian menggunakanmodel Kemmis dan Mc Taggart yaitu perencanaan, tindakan/pelaksanaan, pengamatan, refleksi. Instrumen penelitian yang digunakan yaitu lembar observasi perencanaan pembelajaran dan pelaksanaan pembelajaran, lembar observasi siswa dan lembar kerja siswa. Jumlah subjek pada penelitian ini 14 siswa terdiri 7 siswa laki-laki dan 7 siswa perempuan.Hasilpenelitian menunjukan: (1) Kemampuan guru dalam merencanakan pembelajaran meningkat menjadi 0,19 dari nilai rata-rata siklus I 3,38 sedangkan siklus II 3,57. (2) Kemampuan guru dalam pelaksanaan pembelajaran menunjukan peningkatan 0,29 dari nilai rata-rata siklus I 3,28 sedangkan siklus II 3,57. (3) Hasil berpikir kritis siswa juga meningkat 18,30, dari nilai rata-rata siklus I yaitu 62,50 sedangkan siklus II80,80. Dilihat dari nilai ketuntasan hasil belajar siswa dengan Kriteria Ketuntasan Minimum (KKM) yaitu 60, pada siklus I nilai rata-rata 67,57 dan siklus  II77,85 artinya pembelajaran IPS pada materi peristiwa kedatangan bangsa barat dinyatakan tuntas telah mencapai kriteria ketuntasan minimum, dengan menerapkan model pembelajaran konstruktivisme pada mata pelajaran IPS tentang peristiwa bangsa barat maka berpikir kritis siswa meningkat. Kata Kunci: Penerapan, Model Konstruktivisme,Berpikir Kritis Siswa, MataPelajaran Ilmu Pengetahuan Sosial